Allelopathic effects of glucosinolate breakdown products in Hanza [Boscia senegalensis (Pers.) Lam.] processing waste water - Rivera-Vega, Loren J.; Krosse, Sebastian; de Graaf, Rob M.; Garvi, Josef; Garvi-Bode, Renate D.; van Dam, Nicole M. (Frontiers in Plant Science, 2015)
Boscia senegalensis is a drought resistant shrub whose seeds are used in West Africa as food. However, the seeds, or hanza, taste bitter which can be cured by soaking them in water for 4–7 days. The waste water resulting from the processing takes up the bitter taste, which makes it unsuitable for consumption. When used for irrigation, allelopathic effects were observed. Glucosinolates and their breakdown products are the potential causes for both the bitter taste and the allelopathic effects. The objectives of this study are to identify and quantify the glucosinolates present in processed and unprocessed hanza as well as different organs of B. senegalensis, to analyze the chemical composition of the processing water, and to pinpoint the causal agent for the allelopathic properties of the waste water. Hanza (seeds without testa), leaves, branches, unripe, and ripe fruits were collected in three populations and subjected to glucosinolate analyses. Methylglucosinolates (MeGSL) were identified in all plant parts and populations, with the highest concentrations being found in the hanza. The levels of MeGSLs in the hanza reduced significantly during the soaking process. Waste water was collected for 6 days and contained large amounts of macro- and micronutrients, MeGSL as well as methylisothiocyanate (MeITC), resulting from the conversion of glucosinolates. Waste water from days 1–3 (High) and 4–6 (Low) was pooled and used to water seeds from 11 different crops to weeds. The High treatment significantly delayed or reduced germination of all the plant species tested. Using similar levels of MeITC as detected in the waste water, we found that germination of a subset of the plant species was inhibited equally to the waste water treatments. This confirmed that the levels of methylisiothiocyanate in the waste water were sufficient to cause the allelopathic effect. This leads to the possibility of using hanza waste water in weed control programs.